BOOK REVIEW: Women Founders of Waqf (Vakıf Kuran Kadınlar) - Rahmany, Faizah Aulia (International Journal of Waqf, 2025)
The book Vakıf Kuran Kadınlar (Women Founders of Waqf) is a collection of 14 scientific papers resulting from the 2018 "Waqf Week" symposium in Istanbul, which documents the strategic role of women in the Islamic philanthropic tradition of the Seljuk and Ottoman eras. Through historical, architectural, and sociological approaches, this book reveals the economic independence of women from various social strata—ranging from the Valide Sultan to the general public. The authors' analysis proves that women's waqf was a vital instrument in credible social policy through the use of primary data, such as waqf deeds (vakfiye) and accounting books (muhasebe defterleri). Overall, this book successfully portrays Muslim women as visionary drivers of civilization with strong economic sovereignty.